Quercetin induces an immunoregulatory phenotype in maturing human dendritic cells - Michalski, Julia; Deinzer, Anja; Stich, Lena; Zinser, Elisabeth; Steinkasserer, Alexander; Knippertz, Ilka (Immunobiology, 2020)
The aryl hydrocarbon receptor (AhR) is an environmental sensor and ligand-activated transcription factor that is critically involved in the regulation of inflammatory responses and the induction of tolerance by modulating immune cells. As dendritic cells (DCs) express high AhR levels, they are efficient to induce immunomodulatory effects after being exposed to AhR-activating compounds derived from the environment or diet. To gain new insights into the molecular targets following AhR-activation in human monocyte-derived (mo)DCs, we investigated whether the natural AhR ligand quercetin or the synthetic ligand 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) modulates the function of human moDCs regarding their capability to prime naïve T cells or to migrate. As only quercetin, but not TCDD, impaired T cell activation and migration of LPS-matured DCs (LPS-DCs), we analyzed the mode of action of quercetin on moDCs in more detail. Here, we found a specific down-regulation of the immunomodulatory molecule CD83 through the direct binding of the activated AhR to the CD83 promoter. Furthermore, treatment of LPS-DCs with quercetin resulted in a reduced production of the pro-inflammatory cytokine IL-12p70 and in an increased expression of the immunoregulatory molecules disabled adaptor protein (Dab) 2, immunoglobulin-like transcript (ILT)-3, ILT4, ILT5 as well as ectonucleotidases CD39 and CD73, thereby inducing a tolerogenic phenotype in quercetin-treated maturing DCs. Overall, these data demonstrate that quercetin represents a potent immunomodulatory agent to alter human DC phenotype and function, shifting the immune balance from inflammation to resolution.
CRIS-Team Scopus Importer:2020-03-10
Keywords: Aryl hydrocarbon receptor; Dendritic cells; Quercetin; Regulatory T cells; TCDD; Tolerance